The Values of Local Wisdom in Wawacan Pandita Sawang Manuscripts - Suherman, Agus; Ma’mun, Titin Nurhayati; Darsa, Undang Ahmad; Ikhwan, Ikhwan (UPI, 2021)
Abstract:Â Local wisdom is believed to be a form of internalization of the values embraced by a particular society or community, which are maintained and disseminated from generation to generation, both through oral and written traditions, one of which is through Wawacan Pandita Sawang manuscripts. Employing a qualitative descriptive approach and philological methods, this study is aimed to explore the values of local wisdom contained in the ancient Sundanese manuscripts. The results showed that the local wisdom recorded in the ancient manuscripts has long been lived and practiced by the people, so that it has formed the character of Sundanese people in carrying out their lives, especially those related to the relationship between humans and God, humans and humans, and humans with their environment. Therefore, the study of this manuscript will reopen and at the same time revitalize the values of local wisdom that once lived in Sundanese society as a comparison to develop values of the present time.Â